Spain : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Spain. (IMF Staff Country Reports; Country Report ;, 2018)
Spain's economy has continued to grow strongly, reflecting its improved fundamentals. However, especially the young generation still faces daunting economic challenges. In the meantime, several downside risks are clouding the medium-term outlook. Externally, they comprise sudden changes in investors' global risk appetite, escalating global protectionism, and weakening conditions in emerging economies. Domestically, they include pressure to reverse reforms, continued procyclical fiscal policy, and prolonged uncertainty related to Catalonia. These could hurt the economy particularly in an environment of high public debt and structural unemployment as well as sluggish productivity growth, which is set to slow Spain's income convergence.